Resistance of lactic acid bacteria pig' isolated in faeces and their antagonistic capacity against indicative microorganisms (Revista de Ciências Agroveterinárias, 2006)
Lactic acid bacteria (LAB) were isolated from the faeces of nearly 40 healthy pigs, with different ages. The isolates were selected previously, based on the coloration in All Purpose Tween (APT) agar modified by the addition of 0,004% of purple bromocresol and 0,5% of calcium carbonate, on their morphology and on the coloration in gram and catalase activity. Approximately 50% of the isolated colonies presented morphology of Gram-positive cocos/bastonetes, negative catalase and yellow colonies when cultivated in modified APT agar, being classified as LAB. These isolates of pig faeces were compared by their ability to resist the pH 3.0, to grow in the presence of bile salts for 3 hours and by their antagonistic capacity against the indicative microrganisms (Salmonella typhi ATCC 6539, Campylobacter jejuni ATCC 29428, Escherichia coli ATCC 11229, Staphylococcus aureus ATCC 6538 and Enterococcus faecalis ATCC 19433). Only 18% of the isolates presented less than 1 Decimal Reduction (DR) when cultivated in the presence of pH 3.0. Nearly 36.5% reduced from 1 to 2 DR and 45.5% had more than 2 DR. No isolate had the capacity to grow in specific means with the adjusted pH for 3.0. About 36.5% of the isolates grew in cultivation medim modified with the addition of 0.3% of bile salts, 59% of isolates had decimal reduction smaller or equal to 2 and 4.5% presented decimal reduction larger than 2 DR. The 12 isolates that presented larger resistance to the pH 3.0 and resisted in cultivation medium added of bile salts were selected for the antagonism analysis. No inhibition halo was detected among the isolates, indicating a possible simultaneous growth to produce a probiotic. All the evaluated isolates produced an inhibition halo on at least two of the tested indicative microrganisms.
Keywords: ntagonism; monogastric; pH; bile salts; probiotic; pig.